Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 9618199 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Corvus Linnaeus, 1758", "BasisOfRecord is Human Observation" ] } The dataset includes 9618199 records from 692 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0075530-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences